2023
DOI: 10.3899/jrheum.2022-0827
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferons in Autoimmunity: Implications in Clinical Phenotypes and Treatment Response

Abstract: Type I interferon (IFN-I) is thought to play a role in many systemic autoimmune diseases. IFN-I pathway activation is associated with pathogenic features, including the presence of autoantibodies and clinical phenotypes such as more severe disease with increased disease activity and damage. We will review the role and potential drivers of IFN-I dysregulation in five prototypic autoimmune diseases: systemic lupus erythematosus, dermatomyositis, rheumatoid arthritis, primary Sjogren syndrome, and systemic sclero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 181 publications
0
2
0
Order By: Relevance
“…The elevated activity of type 1 interferon signaling is closely associated with the susceptibility to autoimmune diseases such as systemic lupus erythematosus, Sjögren's syndrome, and rheumatoid arthritis 58 . Counterintuitively, we consistently observed an upregulation of type 1 interferon-associated genes in multiple blood cell populations of BP patients in the remission stage, including pDCs, B cells, CD8 + T cells, and NK cells (Figures S2D, S3C, 5G and 6F).…”
Section: Discussionmentioning
confidence: 99%
“…The elevated activity of type 1 interferon signaling is closely associated with the susceptibility to autoimmune diseases such as systemic lupus erythematosus, Sjögren's syndrome, and rheumatoid arthritis 58 . Counterintuitively, we consistently observed an upregulation of type 1 interferon-associated genes in multiple blood cell populations of BP patients in the remission stage, including pDCs, B cells, CD8 + T cells, and NK cells (Figures S2D, S3C, 5G and 6F).…”
Section: Discussionmentioning
confidence: 99%
“…Type I interferon (IFN-I) is known to perform a crucial function in the pathophysiology of autoimmune diseases, particularly in the progression of SjS ( 95 , 96 ). Interestingly, studies indicate that the most strongly linked differentially methylated positions and regions in SjS patients are situated within genes regulated by type I interferon ( 13 ).…”
Section: Role Of Dna Methylation In Sjsmentioning
confidence: 99%
“…For type I IFNs, plasma proteomic analysis revealed that higher circulating levels of IFNA5 were associated with a higher relative wall thickness in women, but not in men ( 157 ). It may be that determination of a type I IFN signature, as has been done in SLE for instance ( 42 , 158 ), may offer greater prognostic value than measurement of individual IFNs. However, even amongst patients with SLE who often exhibit a strong type I IFN response, a type I IFN signature has not been robustly associated with CVD ( 44 ).…”
Section: Introductionmentioning
confidence: 99%